A Qualitative Study The Optimalization Of Pick UpZone Area - Defri Adityo, Moh; Sudrajat, Sudrajat; Utomo, Wasito (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan is one of the airports managed by PT Angkasa Pura I. At this airport there are 2 sides, namely landside (land side) and airside (air side), on the landside (land side) there are pick up zone area facilities at the arrival terminal. This study aims to determine the correlation between variable X and variable Y by using a type of qualitative descriptive research, namely whether the pick up zone area at the arrival terminal has been optimized and in accordance with applicable rules. So from this description, the researcher took the title "Optimization of the pick up zone area at the arrival terminal to break down congestion at Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan" The formulation of the problem in this study is how to break down congestion and how to optimize the pick up zone area at the arrival terminal at Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan. With data collection methods in the form of observations, interviews, questionnaires, and conducting literature studies and documenting research objects. In the results of the study, the level of correlation between variable X and variable Y was 0.9, which is a very high, very strong, reliable correlation. Then it can be concluded that there is a need for optimization in the arrival terminal pick up zone area by returning the configuration of lane use according to the rules and utilizing empty areas in the pick up zone as a step to minimize the level of congestion at Sultan Aji Muhammad Sulaiman Sepinggan International Airport Balikpapan